Prognostic Association of TERC, TERT Gene Polymorphism, and Leukocyte Telomere Length in Acute Heart Failure: A Prospective Study - Li, Yanxiu; Cheang, Iokfai; Zhang, Zhongwen; Yao, Wenming; Zhou, Yanli; Zhang, Haifeng; Liu, Yun; Zuo, Xiangrong; Li, Xinli; Cao, Quan (Frontiers in Endocrinology, 2021)
Background Telomere length and telomerase are associated in development of cardiovascular diseases. Study aims to investigate the associations of TERC and TERT gene polymorphism and leukocyte telomere length (LTL) in the prognosis of acute heart failure (AHF). Methods Total 322 patients with AHF were enrolled and divided into death and survival group according to all-cause mortality within 18 months. Seven single nucleotide polymorphisms (SNPs) of TERC and TERT were selected. Baseline characteristics, genotype distribution and polymorphic allele frequency, and genetic model were initially analyzed. Genotypes and the LTL were determined for further analysis. Results Compared to carrying homozygous wild genotype, the risk of death in patients with mutated alleles of 4 SNPs- rs12696304(G>C), rs10936599(T>C), rs1317082(G>A) and rs10936601(T>C) of TERC were significantly higher. The dominant models of above were independently associated with mortality. In recessive models, rs10936599 and rs1317082 of TERC, rs7726159 of TERT were independently associated with long-term mortality. Further analysis showed, in haplotype consisting with TERC - rs12696304, rs10936599, rs1317082 and rs10936601, mutant alleles CCAC and wild alleles GTGT were significant difference between groups (P<0.05). CCAC is a risk factor and GTGT is a protective factor for AHF patients. Relative LTL decreased over age, but showed no difference between groups and genotypes. Conclusions The SNPs of TERC and TERT are associated with the prognosis of AHF, and are the independent risk factors for predicting 18-month mortality in AHF.